Impact of ankle injuries on joint range of motion and muscle viscoelasticity in female amateur volleyball athletes - Eunsook Sung (BMC Sports Science, Medicine and Rehabilitation)
Abstract Introduction This study aimed to compare ankle joint range of motion (ROM) and muscle viscoelastic properties in female amateur volleyball players with a history of ankle sprain (AS group) and without (non-AS group). Methods Forty-one female participants were included in the study: 25 in the AS group and 16 in the non-AS group. Ankle ROM was measured for inversion (IV), eversion (EV), plantar flexion (PF), and dorsiflexion (DF). Viscoelastic properties were assessed in the tibialis anterior (TA), medial gastrocnemius (MG), lateral gastrocnemius (LG), and peroneus longus (PL) muscles. Results A significant difference in DF ROM was observed between the AS and non-AS groups (p = 0.030). Muscle frequency was significantly higher for TA (p = 0.010), MG (p = 0.008), and LG (p = 0.008) in the AS group. Additionally, muscle stiffness in TA (p = 0.010), MG (p = 0.014), LG (p = 0.021), and PL (p = 0.049) was significantly greater in the AS group. Significant differences in relaxation were found in TA (p = 0.010) and PL (p = 0.032), while creep differences were noted in TA (p = 0.007). Conclusions These findings suggest that ankle sprain may lead to persistent alterations in muscle mechanical properties and joint mobility, highlighting the importance of comprehensive assessment and targeted rehabilitation of all related muscles to prevent recurrent injuries and optimize recovery in female volleyball players.